‘Don’t send us a cake, and then let us drown again’: remembering and forgetting Cyclone Gabrielle - Luke Goode; Suzanne Woodward; Steve Matthewman; Peter Simpson (Kōtuitui)
We present a critical analysis of news coverage during the one-year anniversary of Cyclone Gabrielle in Aotearoa New Zealand. This disaster raised important questions surrounding emergency preparedness, infrastructural vulnerability, climate change, adaptation, future land-use policies and managed retreat. In the immediate aftermath, Cyclone Gabrielle was repeatedly framed as a ‘wake-up call’ demanding serious attention be given to the increasing risks from future extreme weather events. While media and public attention to Cyclone Gabrielle at the national level dropped rapidly once emergency conditions abated, the one-year anniversary saw major national news outlets renew attention to the disaster. In addition to commemorating lost lives and recognising the ongoing struggles of impacted communities, anniversary news coverage afforded a platform for reflective analysis of the disaster’s implications for the future that was not possible during the initial emergency phase a year earlier: it represented an opportunity to look back at the disaster in order to look forward. We evaluate how and to what extent this was taken up by four major national news outlets, identifying some significant limitations with potentially detrimental consequences for democratic future-making.